Intestinal Parasitic Infections and Eosinophilia: A Cross-sectional Study among Primary School-aged Children in Medan, Indonesia - Rozi, Muhammad F; Darlan, Dewi M; Rahmawati, Rodiah; Siregar, Dewi IS (International Journal of Human and Health Sciences (IJHHS), 2020)
Background:Intestinal parasitic infections (IPIs) anditsimplication, such as malnutrition, growth stunting, anemia, and concentration impairment, still become a global burden. The primary immune cell that firstly involved in counteracting parasitic invasion is eosinophil. Therefore, higher levels of eosinophils could be suspected of havinga parasitic infection. Objective: Our study aimed to revealthe prevalence of IPIs and its correlation with eosinophilia. Material and Methods: The study was located in two different public primary schools,Public Primary School 060925 Harjosari 1, Amplas, Medan, Indonesia and Public Primary School 101747 Hamparan Perak, Deli Serdang, Indonesia which enrolled 132 primary school children aged 8-12 years graded III-VI, consisting of 22 males and 110 females,who had met the inclusion criteria between May and October 2016. Parasitology examination was carried out at the Department of Parasitology, Faculty of Medicine, Universitas Sumatera Utara using Kato-Katz, Lugol, trichrome, and modified acid-fast stain. Results: The study found intestinal protozoa infections were the most common IPIs in the population, Giardia lamblia as the most prevalent species (37.1%), while hookworm with the fewest findings (2.8%). Additionally, the statistical analysis proved a significant correlation between IPIs and eosinophilia (p-value 0.021; 95% CI 1.13-5.58). Conclusion: eosinophilia patients with profound clinical manifestation should be further assessed to be considered for the administration of anti-parasitic medication. International Journal of Human and Health Sciences Vol. 04 No. 04 October’20 Page : 277-281